Pengaruh Reformasi Administrasi Perpajakan dan Tax Amnesty Pada Kepatuhan WPOP Dengan Preferensi Risiko Sebagai Pemoderasi - Erviana Dewi, I Gusti Ayu Putu; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The purpose of this study was to determine the effect of tax administration reforms and tax amnesty on individual taxpayer compliance with risk preferences as moderating (studies in North Badung North Sumatra 2018 KPP). Respondents in this study as many as 100 Individual Taxpayers who participated in the tax amnesty and registered at the North Badung North KPP 2018, were calculated using the Slovin formula with the method of determining accidental sampling. The data analysis technique of this study uses Moderated Regression Analysis (MRA). The conclusion from the results of this study is that tax administration reform has a positive effect on individual taxpayer compliance and tax amnesty does not affect individual taxpayer compliance. Risk preference weakens the relationship between tax administration reform on individual taxpayer compliance and strengthens the relationship between tax amnesty on people's taxpayer compliance. Keywords: Tax administration reform, tax amnesty, risk preference, WPOP compliance